Peace, order, and cleanliness award - College of Computer Studies-De La Salle University, Manila (Animo Repository, 2001)
The College of Computer Studies was given the Peace, Order, and Cleanliness Award for having the least discipline disturbance in the University during the Student Awards 2001.